Test Antioxidant Activity Using the DPPH Method (1,1 Diphenyl-2-picryhidrazyl) in the Ethyl Acetate Fraction of Black Turmeric (Curcuma caeseae) - H. Ambo Lau, Sulfiyana; Kadang, Yuniharce; Anggraeni, Helin (Politeknik Sandi Karsa, 2022)
The purpose of this study was to determine the antioxidant activity with the IC50 value contained in black turmeric (Curcuma cease) rhizome extract using the DPPH (1,1 Diphenyl-2-picryhidrzyl) method. Black turmeric samples were macerated with 96% ethanol solvent. Identification of phenolic compounds produces a purple solution; this indicates that a positive sample containing phenolic compounds. The determination of the IC50 value was carried out by adding the DPPH reaction to each concentration of the sample solution and the vitamin C comparator at the maximum DPPH wavelength of 516 nm. Research has been carried out by quantitatively testing Black turmeric extract (Curcuma caeseae) showing moderate antioxidant activity, with an IC50 value of 144.47 ppm because it is in the IC50 range of 100 – 150 ppm, while vitamin C used as a standard in this study has activity very strong antioxidant 14.0970 ppm because it is in the IC50 value range of less than 50 ppm.